Different functional bio-scaffolds share similar neurological mechanism to promote locomotor recovery of canines with complete spinal cord injury. (September 2019) - Liu, Dingyang; Li, Xing; Xiao, Zhifeng; Yin, Wen; Zhao, Yannan; Tan, Jun; Chen, Bing; Jiang, Xingjun; Dai, Jianwu
Abstract: Many studies have shown that rodents exhibit a certain degree of spontaneous motor function recovery even if they suffer from spinal cord complete transection injury. However, the characteristics of spontaneous locomotor recovery and its associated neurobiological mechanisms are unclear. In this study, we observed that spontaneous locomotor function recovery of hind limbs could also be detected in a canine thoracic (T8) spinal cord complete transection model. In addition, the spontaneous locomotor recovery of canines could be further promoted by chronic implantation of Taxol- or human bone marrow mesenchymal stem cell-modified bio-scaffolds. Moreover, functional bio-scaffolds implantation promoted locomotor outcome could be significantly weakened (drop to the spontaneous recovery level) but not totally abolished by resection in the lesion site. The neurological mechanism for functional bio-scaffolds improved locomotor outcome was primarily dependent on the formation of neuronal bridging but not the long-distance regeneration of descending motor axons throughout the lesion gap. Besides that, we found that spontaneously achieved locomotor recovery of hind limbs was unable to be weaken by repetitive resection of the lesion area, indicating the mechanism for spontaneous locomotor recovery was independent on functional neurological bridging throughout the lesion gap.